AI weapon systems in future war operations; strategy, operations and tactics. Issue 1 (2nd January 2022) - Ploumis, Michail
Abstract: In the future, at the strategic, operational and tactical level of warfare, the substitution of the human will and action by autonomous AI weapon systems appears quite probable. These systems are already being used and have the capability to successfully deal with threats faster than humans. The countering of AI weapon systems will pose a great challenge in a future war. In this article, the case is made that for the AI weapon systems to be defeated, unconventional cognition will be required.